Gerontological social work in action : anti-oppressive practice with older adults, their families, and communities - Hulko, Wendy, 1970- (New York, NY : Routledge, 2020)
'Gerontological Social Work in Action introduces'anti-oppression gerontology' (AOG), a critical approach to social work with older adults, their families, and communities. AOG principles are applied to direct and indirect practice and a range of topics of relevance to social work practice in the context of a rapidly aging world. Weaving together stories, theories, research, and practical tools, this unique textbook prompts social workers to think differently and push back against oppressive forces. It pays attention to issues, realities, and contexts which are largely absent in social work education and gerontological practice. This includes important developments in our understanding of age/ism; theories of aging and social work; sites and sectors of health and social care; managing risk and frailty; moral, ethical and legal questions about aging, including medical assistance in dying; caregiving; dementia and citizenship; trauma, and much more. This textbook should be considered essential reading to social work students new to aging and/or seeking to specialize as well as others interested in the application of anti-oppressive principles to working and researching with older adults'--
Includes bibliographical references and index.
Keywords: Social work with older people; Older people -- Services for; Social gerontology